Allied health surge capacity in Australian intensive care units during the COVID-19 pandemic: A cross-sectional survey. Issue 1 (January 2023) - Paykel, Melanie; Ridley, Emma; Freeman-Sanderson, Amy; Ramanan, Mahesh; Booth, Sarah; Cook, Katrina; Ip, Kelvin; De Gori, Mary; Blackshaw, Julia; Markham, Donna; Downie, Sharon; Haines, Kimberley
Abstract: Background: Based on the early international COVID-19 experience, it was anticipated that intensive care services and workforces in Australia would be placed under similar pressure. While surge capacity of medical and nursing workforces was estimated, little was known about baseline allied health staffing, making it difficult to estimate surge capacity and coordinate planning. Objectives: The purpose of this study was to (i) capture baseline allied health staffing levels in Australian adult intensive care units (ICUs) prior to the COVID-19 pandemic emergence in Australia and (ii) describe the allied health pandemic planning and surge response in Australian ICUs during the early waves of the pandemic. Methods: This was a cross-sectional, investigator-devised, prospective survey study. The survey was administered via the national chief allied health network to a convenience sample of senior ICU allied health clinicians at hospitals throughout Australia. Results: A total of 40 responses were received from tertiary and metropolitan hospitals; 12 (30%) physiotherapists and eight (20%) occupational therapists were the most frequent respondents. Prior to the COVID-19 pandemic, 28 (70%) allied health respondents had a mean (interquartile range) of 1.74 (2.00) full-time equivalent staff designated to the ICU, where these ICUs had a mean of 21.53 (15.00) ventilator beds. Few respondents serviced their ICU on a referral-only basis and did not have dedicated ICU full-time equivalent (12; 20%). Surge planning was mostly determined by discussion within the ICU, allied health department, and/or respective disciplines. This approach meant that allied health staffing and associated decision-making was ad hoc at a local level. Conclusions: The baseline rate of allied health coverage in Australian ICUs remains unknown, and the variability across allied health and within the specific disciplines is undetermined. Further research infrastructure to capture ICU allied health workforce data is urgently needed to guide future pandemic preparedness.